Recording tour of the Tswana tribe: Western Transvaal and Bechuanaland Protectorate, October - November, 1959 - Tracey, Hugh (International Library of African Music, 1959)
Little or nothing has been written or recorded in the last 25 years on the subject of Tswana music, and when the Field Recording Unit cf the Library set out to try to fill part of this gap, careful preparations were made beforehand. On account of the relatively short distances from the Library Headquarters which were involved and from well founded suspicions that the Tswana were not inclined to be co-operative, it was decided to make a preliminary tour in order to visit most of the Chiefs and villages where we intended to record.
Keywords: African Music